A review of berotralstat for the treatment of hereditary angioedema. (1st February 2023) - Farkas, Henriette; Balla, Zsuzsanna
ABSTRACT: Introduction: Hereditary angioedema due to C1-inhibitor deficiency (C1-INH-HAE) imposes a significant disease burden on patients and their families. Unpredictable episodes of angioedema, which can lead to life-threatening conditions, have a significant impact on the quality of life of the patient. The fundamental aim of the treatment of C1-INH-HAE is to ensure that patients can lead a normal life. The most effective way to do this is to prevent the onset of angioedema attacks. Areas covered: This review gives a brief overview of the safety and efficacy of the oral kallikrein inhibitor berotralstat in C1-INH-HAE disease. It provides a comprehensive synopsis of the results of the first clinical trials with a targeted oral kallikrein inhibitor (APeX-1 [NCT02870972]; ZENITH-1 [NCT03240133]; APeX-2 [NCT03485911]; APeX-S [NCT03472040]; APeX-J [NCT03873116]), reviewing evidence on the efficacy and safety of the drug, and placing berotralstat on the spectrum of long-term prophylactic therapeutic options. Expert opinion: The availability of the first targeted oral prophylactic drug, the kallikrein inhibitor berotralstat, in 2021, is a milestone in the treatment of patients with hereditary angioedema.